Prevalence of Gestational Diabetes Mellitus and Pregnancy Outcomes in Women with Risk Factors Diagnosed by IADPSG Criteria at Bhumibol Adulyadej Hospital - Kanjana Kanthiya; Wiyada Luangdansakul; Petch Wacharasint; Sinart Prommas; Buppa Smanchat (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objective:To determine the prevalence and clinical outcomes of gestational diabetes mellitus (GDM), defined by IADPSG criteria, in pregnant women who are at risk of GDM.Study design: Descriptive study.Material and Method: We studied pregnant women who visited the antenatal clinics at Bhumibol Adulyadej Hospital between July 1, 2011 and December 31, 2012 and had risk factors of GDM. The diagnosis of GDM was defined using the IADPSG criteria. Primary outcome was the prevalence of GDM and the secondary outcomes were pregnancy related complications which included maternal and neonatal complications.Results: A total of 6,324 pregnancy women, 164 patients were diagnosed GDM. The prevalence of GDM was 2.6%. The most common clinical risk factor for GDM was age ≥30 years (75.4%). The most common maternal and neonatal complication were pregnancy induced hypertension (PIH) (12.7%) and hypoglycemia (47.6%). GDM women were significantly different from non-GDM women in PIH, primary cesarean section, hypoglycemia, Apgar <7, and NICU admission. Pregnancy outcomes between GDM A1 and A2 were significantly different. GDM A2 increased the rate of cesarean section, hypoglycemia, and NICU admission. Conclusion: Using the IADSP criteria, the prevalence of GDM was 2.6%. Compared to non-GDM regnant women, adversed pregnancy outcomes were significantly higher in GDM pregnant women